PENGEMBANGAN MEDIA AJAR DIORAMA BERBASIS STEM PADA MATERI METAMORFOSIS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS SISWA KELAS III SEKOLAH DASAR - Melly Sundari Sitorus; Santi Sirait; Asri Jully Syani; Neni Hermita; Rifqa Gusmida Syahrun Barokah (STKIP Subang, 2026)
This research aims to develop media teaching metamorphosis based on STEM (Science, Technology, Engineering, and Mathematics) that is feasible and effective in improving thinking skills. This exploration is inspired by decisive reasoning abilities and understudies’ comprehension of the transformation learning of science material which isn’t amplified because of the growing experience which actually doesn’t utilize the right methodology and learning media. The motivation behind this review was to decide the attainability of STEM-based lifelike model media to further develop the decisive reasoning abilities of 3th grade primary school understudies. This sort of examination is Innovative work (Research and development) research utilizing the Borg and Gall model. The procedures of this research include several stages, namely analisis, design, development, implementation, and evaluation. Data were ccollected through observation, questionnaires, and tests. The feasibility of the developed media was determined based on validation results, while its effectiveness was measured by comparing students critical thinking skills before and after using the media. The results show that the STEM-based lifelike model media is feasible to be used in the learning process and is effective in improving the critical thinking skills of third grade primary school students. Therefore, this media can be used as an alternative learning tool to support science learning, especially in metamorphosis material, so that students become more active and better understand the learning content.